Pharmaceutical composition of non-steroidal anti-inflammatory drugs - Basri, Mahiran; Chong, Kah Huong; Kassim, Anuar; Salleh, Abu Bakar; Abdul Rahman, Mohd Basyaruddin; Raja Abdul Rahman, Raja Noor Zaliha; Shohaimi, Shamarina; Shamsuddin, Ahmad Fuad; Basri, Hamidon; Mohd Noor, Mohd Azmin; Abdul Sattar, Munavvar (2009)
A pharmaceutical composition prepared in the form of nano-emulsion comprises an aqueous medium; a non-steroidal anti-inflammatory drug; at least one type of emulsifier; a lipophilic mixture containing a mixture of a fatty acid ester and an optionally added aliphatic C2 to C8 alcohol characterized in that the mixture of fatty esters consists of fatty esters with carbon chain ranging from C30 to C36.